Enhanced electrochromic performances of Polythieno[3, 2-b]thiophene with multicolor conversion via embedding EDOT segment. (20th December 2018) - Xue, Yu; Xue, Zexu; Zhang, Wenwen; Zhang, Wenna; Chen, Shuai; Lin, Kaiwen; Xu, Jingkun
Abstract: A heterocyclic oligomer, thieno[3, 2-b]thiophene (TT) end-capped famous 3, 4-ethylenedioxythiophene (EDOT) unit and their electrosynthesized polymer P(TT-EDOT-TT) have been facilely achieved. To in-depth understand the effects of structural modification on physico-chemical properties and electrochromic performances of monomers and/or polymers, the absorption spectroscopy, electrochemistry, micromorphology, and spectroelectrochemistry were systematically studied. In contrast to TT and EDOT, TT-EDOT-TT possessed extended π-conjugation and narrowed band gap in molecular level. Through carefully comparison with PTT, it has been found that the electrochromic performances of P(TT-EDOT-TT) film exhibited much higher optical contrast (69%, while 3% for PTT in the near-infrared region) and superior coloring efficiency (255.3 cm 2  C −1, while 36.8 cm 2  C −1 for PTT), and switching times (within 1 s, while more than 9 s for PTT). Notably, P(TT-EDOT-TT) film can achieve the mutual conversion between RGB primary colors (red–green–blue) under variable voltages, which hold quite promising for display applications. Graphical abstract: Highlights: Facilely preparation method. Excellent electrochromic performances. Multicolor conversion between RGB color space.